Hi, you haven't provided the programing language in which you need the code, I'll just explain how to do it using Python, and you can apply a similar method for any programming language.
Answer:
1. def pyramid_volume(base_length, base_width, pyramid_height):
2. volume = base_length*base_width*pyramid_height/3
3. return(volume)
Explanation step by step:
- In the first line of code, we define the function pyramid_volume and it's input parameters
- In the second line, we perform operations with the input values to get the volume of the pyramid with a rectangular base, the formula is V = l*w*h/3
- In the last line of code, we return the volume
In the image below you can see the result of calling the function with input 4.5, 2.1, 3.0.
Answer: 1766.667 Ω = 1.767kΩ
Explanation:
V=iR
where V is voltage in Volts (V), i is current in Amps (A), and R is resistance in Ohms(Ω).
3mA = 0.003 A
Rearranging the equation, we get
R=V/i
Now we are solving for resistance. Plug in 0.003 A and 5.3 V.
R = 5.3 / 0.003
= 1766.6667 Ω
= 1.7666667 kΩ
The 6s are repeating so round off to whichever value you need for exactness.
Answer: Option A is correct -- 2.6 at% Pb and 97.4 at% Sn.
Explanation:
Option A is the only correct option -- 2.6 at% Pb and 97.4 at% Sn. While option B, which is 7.6 at% Pb and 92.4 at% Sn. and option C, which is 97.4 at% Pb and 2.6 at% Sn. and option D, which is 92.4 at% Pb and 7.6 at% Sn. are wrong.
C is your answers!!!!!$3&2)//
Answer: ε₁+ε₂+ε₃ = 0
Explanation: Considering the initial and final volume to be constant which gives rise to the relation:-
l₀l₀l₀=l₁l₂l₃
![\frac{lo*lo*lo}{l1*l2*l3}=1.0](https://tex.z-dn.net/?f=%5Cfrac%7Blo%2Alo%2Alo%7D%7Bl1%2Al2%2Al3%7D%3D1.0)
taking natural log on both sides
![ln(\frac{(lo*lo*lo)}{l1*l2*l3})=ln(1)](https://tex.z-dn.net/?f=ln%28%5Cfrac%7B%28lo%2Alo%2Alo%29%7D%7Bl1%2Al2%2Al3%7D%29%3Dln%281%29)
Considering the logarithmic Laws of division and multiplication :
ln(AB) = ln(A)+ln(B)
ln(A/B) = ln(A)-ln(B)
![ln(\frac{(l1)}{lo})*ln(\frac{(l2)}{lo})*ln(\frac{(l3)}{lo}) = 0](https://tex.z-dn.net/?f=ln%28%5Cfrac%7B%28l1%29%7D%7Blo%7D%29%2Aln%28%5Cfrac%7B%28l2%29%7D%7Blo%7D%29%2Aln%28%5Cfrac%7B%28l3%29%7D%7Blo%7D%29%20%3D%200)
Use the image attached to see the definition of true strain defined as
ln(l1/1o)= ε₁
which then proves that ε₁+ε₂+ε₃ = 0